Hydrogen sulfide promotes autophagy of hepatocellular carcinoma cells through the PI3K/Akt/mTOR signaling pathway - Wang, Shanshan S.; Dooley, Steven (Cell death & disease, 2017)
Hydrogen sulfide (H2S), in its gaseous form, plays an important role in tumor carcinogenesis. This study investigated the effects of H2S on the cell biological functions of hepatocellular carcinoma (HCC). HCC cell lines, HepG2 and HLE, were treated with NaHS, a donor of H2S, and rapamycin, a classic autophagy inducer, for different lengths of time. Western blotting, immunofluorescence, transmission electron microscopy (TEM), scratch assay, CCK-8 and flow cytometric analysis were carried out to examine the effects of H2S on HCC autophagy, cell behavior and PI3K/Akt/mTOR signaling. Treatment with NaHS upregulated expression of LC3-II and Atg5, two autophagy-related proteins, in HepG2 and HLE cells. TEM revealed increased numbers of intracellular double-membrane vesicles in those cells treated with NaHS. Like rapamycin, NaHS also significantly inhibited expression of p-PI3K, p-Akt and mTOR proteins in HCC cells. Interestingly, the expression of LC3-II was further increased when the cells were treated with NaHS together with rapamycin. In addition, NaHS inhibited HCC cell migration, proliferation and cell division. These findings show that H2S can induce HCC cell apoptosis. The biological function of the gasotransmitter H2S in HCC cells was enhanced by the addition of rapamycin. Hydrogen sulfide influences multiple biological functions of HCC cells through inhibiting the PI3K/Akt/mTOR signaling pathway.
Gesehen am 27.09.2018